Nurse's role during the postpartum period of patients with puerperal mental disorders (Research, Society and Development, 2021)
The present study is about the role of nurses during the postpartum with patients with puerperal mental disorders. The main objective is the importance of the role of nurses during the postpartum period for women with mental disorders in the puerperium. An integrative review was carried out with the following guiding question: “What is the importance of the nurse's performance during the postpartum period, in front of patients with puerperal mental disorders?” The search for publications was performed in Medline, Lilacs, BDENF and Scielo databases. According to the inclusion criteria, ten articles were selected, seven published in the Portuguese language and three published in the English language, with full text available, from March to May 2021, using the following descriptors: “disorders mental disorders”, “postpartum depression”, “pregnancy”, “role of the nurse”. For the discussion, the works were categorized by content similarity, and three discussion categories were built for analysis: “Postpartum depression - A lonely reality in the care of the puerperal woman; "The role of nurses with patients with puerperal mental disorders - The beginning of a long journey" and "Strategies and protocols in assisting mothers with puerperal mental disorders". We conclude that there is a need for the nurse to have knowledge about puerperal mental disorders in order to, thus, accompany the woman in a broad way, offering her comprehensive assistance, from the gestational period until the puerperium, reducing the risk of future injuries your health to that of your baby.